Review and Interpretation of Trends in DNA Barcoding - DeSalle, Rob; Goldstein, Paul (Frontiers in Ecology and Evolution, 2019)
Interpretations and analytical practices surrounding DNA barcoding are reviewed from a compilation of 3,756 papers (as of December 31, 2018) with “DNA Barcode” in the title since 2004. By examining the practice of DNA barcoding in natural history and biodiversity science over this period, we explore the extent to which its purposes, premises, rationale and application have evolved. The number of studies involving identification, taxonomic decisions and the discovery of cryptic species has driven the publication of DNA barcode studies overall. Forensic studies and papers on biological conservation involving DNA barcodes have tracked the ensemble number of studies but rose sharply in 2017. Although neighbor-joining and graphic (tree-based) criteria for species delimitation have been preeminent, analytical paradigms have diversified slightly following the growing availability of tools in the Barcode of Life Database (BoLD). We conclude that the paradigms of DNA barcoding data are likely to persist and, in groups such as Lepidoptera, DNA barcoding has become a widely used tool in taxonomic science. The degree to which systematists will avail themselves of tools for extracting diagnostic data from barcodes remains to be seen.